Contraception and preconception counseling in women with autoimmune disease. (April 2020) - Sammaritano, Lisa R.
Abstract: Appropriate contraception and preconception counseling are critical for women of reproductive age with systemic autoimmune diseases (AIDs) because clinical diagnosis, rheumatology medications, and disease activity may impact the safety or efficacy of certain contraceptives as well as the risk of adverse pregnancy outcomes. The presence of antiphospholipid (aPL) antibodies (anticardiolipin, anti -β2 glycoprotein I, and lupus anticoagulant) is the most important determinant of contraception choice, as women with these antibodies should not receive estrogen-containing contraceptives because of the increased risk of thrombosis. Prepregnancy counseling generally includes the assessment of preexisting disease-related organ damage, current disease activity, aPL antibodies, anti -Ro/SS-A and anti-La/SS-B antibodies, and medication safety in pregnancy. Quiescent AID for six months on pregnancy-compatible medications optimizes maternal and fetal/neonatal outcomes for most patients. Highlights: Contraception is important for women with autoimmune disease because of pregnancy risks associated with disease damage or activity and use of teratogenic medications. Long-acting reversible contraceptives (LARC) are most effective and recommended for women with AID. Prepregnancy assessment includes assessment of disease-related organ damage, level of disease activity, antiphospholipid, anti -Ro/SS-A and/or anti-La/SS-B antibodies, and medications. Good maternal and fetal outcomes are most likely for the patient with AID without severe organ damage and with well-controlled disease on pregnancy-compatible medications.